Microbiome Diversity Across Endangered Primate Populations (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2022)
The gut microbiome represents a critical interface between host physiology, diet, and environment that may mediate host responses to habitat degradation, dietary change, and disease exposure in endangered primate populations. This study characterised faecal microbiome diversity across six endangered primate species spanning four families (Hominidae,Cercopithecidae, Colobidae, Hylobatidae) from 28 wild and semi-captive populations in West Africa, Central Africa, and Southeast Asia, using 16S rRNA amplicon sequencing (V3–V4 region; Illumina MiSeq) of 486 non-invasively collected faecal samples. A mean of 84,240 ± 12,480 high-quality reads per sample were obtained, yielding 2,842 ASVs across the full dataset. Microbiome alpha diversity (Shannon index) declined significantly with population-level habitat disturbance index (HDI; rs = -0.74, p < 0.001) and increased with dietary breadth (rs = +0.68, p < 0.001). Beta diversity (UniFrac distance) was significantly structured by species identity (PERMANOVA R2 = 0.42, p < 0.001), population (R2 =0.18, p < 0.001), and season (R2 = 0.08, p = 0.002). Wild populations showed significantly higher microbiome diversity than conspecific semi-captive populations (Shannon H: 4.82 ± 0.48 vs. 3.64 ± 0.52; t = 6.84, p < 0.001), and lowerFirmicutes:Bacteroidetes ratios (1.84 ± 0.42 vs. 3.42 ± 0.64), consistent with captivity-associated microbiomehomogenisation. LEfSe differential abundance analysis identified 84 ASVs significantly enriched in high-HDI (disturbed) populations, predominantly Enterobacteriaceae and Streptococcaceae, consistent with pathobiont enrichment under habitat stress. These findings identify microbiome diversity loss as a measurable indicator of population-level conservation status and suggest that microbiome restoration through dietary supplementation may be a tractable intervention for captive breeding programme health management.